Pengadaan Koleksi Bahan Pustaka di Kantor Arsip Perpustakaan dan Dokumentasi Kota Padang - Afri Yanti; Bakhtaruddin Nst. (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study was (1) describe the process of acquisition of library collections in tfaced in the procurement process library materials, (3) attempt to overcome these constraints. The data of this study is the acquisition of library materials in KAPD Padang. The data source of this research is the primary source of oral sources as spoken directly by informants as the original speakers. Data were collected through observation and interviews. The findings of the study conducted acquisition of library materials KAPD city of Padang is onlhe Archives, Library and Documentation Padang, (2) determine the constraints y done through purchase, gift/donation as library materials acquisition.